Peningkatan Minat Belajar Ekonomi melalui Model Pembelajaran Problem Based Learning Berbantuan Media Audiovisual Canva - Junita Sari; Yuliana FH (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of the Problem Based Learning model assisted by Canva audiovisual media on the learning interest in economics among eleventh-grade students at SMAN 2 Indralaya Utara. The background of this research stems from several learning issues, such as economics lessons often being unengaging, with students lacking focus and active involvement, necessitating innovations like Problem Based Learning that encourages active participation through solving real-world problems, in line with Vygotsky and Bruner's constructivism theories. This is an experimental research with a Quasi-Experimental Design in the form of a One Group Pretest-Posttest Design. The results show that t_count = 18.895 ≥ t_table = 1.7109, meaning Ho is rejected and Ha is accepted, thus it can be concluded that there is an influence of the Problem Based Learning model assisted by Canva audiovisual media on the learning interest in economics among eleventh-grade students at SMAN 2 Indralaya Utara. The conclusion emphasizes the effectiveness of Problem Based Learning assisted by Canva in making learning more engaging and interactive, as it transforms learning from passive to active, creative, and visual, aligning with modern learning styles. Despite constraints such as the need for Canva premium and limitations focusing only on learning interest, as well as the relatively short research duration for observing long-term impacts.